Beyond the Health Extension Program: Developing a focused approach to improve nutrition in Ethiopia - Zerfu, Taddese Alemu (International Food Policy Research Institute, 2024)
The Ethiopian Health Extension Program (HEP) has long been a cornerstone of the country’s public health strategy, especially in rural and underserved areas. Launched with high hopes in 2003, the HEP aimed to advance health-related Millennium Development Goals (MDGs) and provide essential health services to communities with limited access.